ENTROPIC-METRIC DIAGRAMS OF ASTROPHYSICAL OBJECTS - Zhanabaev, Z.Zh.; Alimgazinova, N.Sh.; Beisebayeva, A.S.; Naurzbayeva, A.Zh. (Recent Contributions to Physics, 2021)
Informational - entropic and generalized metrical characteristics of solar radio-wave radiation and variable stars signals have been determined. It is shown, that suggested new method allows to classify different types of astrophysical signals quantitatively.